The Lyotard reader and guide - Lyotard, Jean-François, 1924-1998 (Edinburgh University Press, 2006)
The first comprehensive anthology of Jean-François Lyotard's writings together with a critical guide.
Keywords: Lyotard, Jean-François, -- 1924-1998 -- Criticism and interpretation.; Lyotard, Jean François -- Critique et interprétation.; Lyotard, Jean-François, -- 1924-1998; PHILOSOPHY -- General.; Criticism, interpretation, etc.